Impact of geographical diversification and limited attention on private equity fund returns - ONG, Victor Hock Keong (Institutional Knowledge at Singapore Management University, 2022)
This study analyzes the effect of geographical diversification on global private equity (PE) fund returns. I find that there is a negative correlation between geographical diversification and PE fund returns. To establish the causality between geographical diversification and PE fund returns, I employ an instrument variable analysis where the instrument used is the stock market capitalization value of the host country where the PE fund is based. My results apply to Net IRR, multiple and DPI as dependent variables used to proxy for PE fund returns in the main regression model. A one standard deviation increase in geographical diversification results in a 18.8 percent reduction in PE fund returns from a Net IRR perspective in the main regression model. Fund age and industry diversification helps mitigate the negative correlation between geographical diversification and returns. Evidence indicates that the relationship between geographical diversification and PE fund returns follows an inverted U shape function. Endogeneity treatments further validates the instruments in the model and reinforces study findings.